2020
DOI: 10.1080/15435075.2020.1818247
|View full text |Cite
|
Sign up to set email alerts
|

Overview of recent developments and the future of organic Rankine cycle applications for exhaust energy recovery in highway truck engines

Abstract: Overall developments in internal combustion engines suggest that the ORC system recovers exhaust heat for further use, increases system performance, and decreases adverse environmental impacts, including greenhouse gas emissions, and particulate matter. This paper presents an overview of crucial advancements in the field of ORC application in commercial vehicles for WHR and continuing developments towards clean fuels and emission regulatory standards. The is review centred on the potential of ORC technology, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…A step even forward could be the use of the heat stored by the engine lubricating agent, used also in terms of preheating the Rankine organic agent. As a consequence, the whole installation efficiency could probably increase by certain percentage units, as already experimented, together with ensuring low emissions' levels and classic fuel economy [17].…”
Section: Further Researchmentioning
confidence: 91%
“…A step even forward could be the use of the heat stored by the engine lubricating agent, used also in terms of preheating the Rankine organic agent. As a consequence, the whole installation efficiency could probably increase by certain percentage units, as already experimented, together with ensuring low emissions' levels and classic fuel economy [17].…”
Section: Further Researchmentioning
confidence: 91%
“…ORC system as a means of exhausting heat recovery has been implemented in some industrial procedures and on-board ship vessels with more than 100 plants operating to generate electricity commercially worldwide [2]. However, the application of this ORC technology on-board mobile vehicles is still a matter of academic studies and laboratory testing because of the adverse effects of added weight and space restrictions on the vehicles [3,4]. Some experimental studies on applying ORC systems for exhaust heat recovery are reported in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Today's concerns about these negative impacts of combustion exhaust emissions; increasingly stringent emission regulations benchmarked on the quantity of CO 2 expulsion from ICEs; and the need for sustainable and efficient deployment of fossil fuel resources in ICEs control the present trends of research and development (R & D) in automobile industries. Therefore, recapturing some portion of the exergy in this waste heat stream, which otherwise is exhausted to the environment, not only mitigate exhaust emissions and their adverse effects but as well lead to thermal efficiency improvement of the model through the generation of additional power to augment the existing one without extra-fuel consumption by the IC engine [2].…”
Section: Introductionmentioning
confidence: 99%